Some features of metal cerium asymptotical behavior - Soldatova, E.D.; Galachenko, T.E. (Condensed Matter Physics, 2006)
The relations between the critical exponents of basic stability characteristics are obtained based on the thermodynamic stability requirements for the generalized one-component system without engaging any hypotheses. The conditions are obtained, where these relations are fulfilled as equalities. The outcomes are applied to the consideration of critical properties of the isomorphic γ–α transition in the metal cerium. It is shown, that for cerium the corresponding relations are fulfilled as equalities. It is also shown, that the equilibrium curve in the P–T phase diagram of cerium continuously passes into the lowered stability curve in the supercritical region, that provides symmetry between its critical exponents. The obtained results are in accord with the scaling law hypothesis without any assumptions about homogeneous functions for the potentials.